2005
DOI: 10.1021/jf0401221
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids and Fat-Soluble Vitamins in Salted Herring (Clupea harengus) Products

Abstract: The fatty acid composition and contents of fat and fat-soluble vitamins of three salted products prepared from Icelandic herring were analyzed. The effects of storage on the products over their shelf life, 6 or 12 months, were investigated. The average oil content of salted, gutted herring and salted fillets in vacuum remained constant, 17 and 12% of wet weight, respectively. In the pickled product the oil content decreased during the 12 months of storage from 13 to 12%. The composition of the products was typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 46 publications
5
19
0
1
Order By: Relevance
“…In fact, as reported in Table 1, the n -3/n -6 ratio was about 8 in both samples due to the low level of n -6 acids and high levels of EPA and DHA. The results presented in this investigation are in agreement with similar study on salted herring (Clupea harengus) products as reported by Aro et al [9], and also with previous studies on the general lipid composition in the ovary of Bluefin Tuna (BFT) T.thynnus by Mourente et al [23] during sex maturation. It is worth to highlight the role of both DHA and EPA in the ovary of this T. thynnus during sex maturation and spawning, in order to better understand the results obtained in our research.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In fact, as reported in Table 1, the n -3/n -6 ratio was about 8 in both samples due to the low level of n -6 acids and high levels of EPA and DHA. The results presented in this investigation are in agreement with similar study on salted herring (Clupea harengus) products as reported by Aro et al [9], and also with previous studies on the general lipid composition in the ovary of Bluefin Tuna (BFT) T.thynnus by Mourente et al [23] during sex maturation. It is worth to highlight the role of both DHA and EPA in the ovary of this T. thynnus during sex maturation and spawning, in order to better understand the results obtained in our research.…”
Section: Resultssupporting
confidence: 93%
“…Fish and fish derivates consumption are recommended by health authorities, not only for their high-quality protein content, but also for being a source of fatty acids considered highly beneficial for human health (n -3 and n -6) [7]. Recently special attention has been paid to the ratio of n -3/n -6 fatty acids because a very high intake of n -6 acids has been recognized to be less desirable [8,9]. Nutritionists believe that the desirable ratio n -3/n -6 should be 5 and that the addition of n -3 polyunsaturated fatty acids (n -3 PUFA) could improve nutritional alue and prevent diseases [10].…”
Section: Resultsmentioning
confidence: 99%
“…The monounsaturated fatty acids (MUFA) constituted the main group of fatty acids in the by-products from both February and November (54 % of total FA). The high amount of MUFAs is characteristic for herring (Hamre et al, 2003;Jensen et al, 2007;Aro, et al, 2005) since herring feeds on small zooplanktonic crustacea rich in the corresponding fatty alcohols in their wax esters (Aro et al, 2005). A higher amount of the polyunsaturated fatty acids was found in the by-products from November compared to February, indicating a decrease in PUFA concentration during the herring season (Hamre et al, 2003;Jensen et al, 2007).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Other significant food sources are fortified items such as margarine, skimmed milk, and orange juice (20,21). Although, in general, fish is a good source of vitamin D, there are considerable differences in vitamin D content between different fish species (13,22). Other important factors are environmental conditions, such as season, and the fat content of the fish (13), but more research is needed in this area.…”
Section: Introductionmentioning
confidence: 99%